Comparison of The Effectiveness of Beetroot Juice with Red Guava Juice in Anemic Pregnant Women - Paramitha, Intan Azkia; Lufar, Nay; Rosidi, Ahyar; Khaqiqi, Kharishma; Fatmawati, Amelia; Syakira, Wijdaningrum (Universitas Islam Jember, 2024)
Anemia is a deficiency of red blood cells where the number of red blood cells decreases, oxygen uptake and blood flow to the brain also decreases. The aim was to compare the effectiveness of beetroot juice and red guava juice in increasing hemoglobin in anemic pregnant women. The method used in writing this article is library research or literature review. The literature used in this research is in the form of journals. Journal searches were carried out using Google Scholar and PubMed databases. Research shows that there is a difference between giving red guava juice and beet juice in terms of hemoglobin levels in pregnant women. The average value before and after administration of red guava juice was 8.4 g/dl to 11.5 g/dl, and the average value before and after administration of beetroot juice was 8.5 g/dlto 10.2 g/dl.